Phytoremediation with hemp (Cannabis sativa L.): a look at hemp's potential for environmental cleanup and economic recovery - Abernathy, Susan M., author; Pilon-Smits, Elizabeth, advisor; Pilon, Marinus, committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2022)
The aim of this thesis study was to test hemp's (Cannabis sativa L.) potential for phytoremediation (environmental clean-up). I tested hemp for tolerance and accumulation of four inorganic pollutants, to evaluate its remediating performance. Hemp has many properties that would make it a likely candidate for phytoremediation however, due to recent regulations, research of this versatile plant has been limited. Phytoremediation is a process of cleaning polluted sites using plants. In this clean-up method, plants may stabilize the pollutant in situ, or take-up the pollutant into the plant tissue. In the latter, there are a few different fates for the pollutant that include degradation, metabolization, sequestration, and/or volatilization. Phytoremediation is a clean process that reestablishes an onsite ecosystem and is a competitive alternative to more conventional scrape-and-remove methods. Hemp is a hardy, fast growing species that produces high biomass. Hemp has deep roots that can be used to reach pollutants deep in the ground. These properties make hemp a potential choice for phytoremediation. Contaminated sites create harsh growing conditions that require hardy plant properties in order for a species to survive. An added benefit to using hemp for remediation is the many economic uses of hemp biomass. Each part of the hemp plant can be used to make goods such as clothing, building material, cosmetics, lotions, animal bedding, fragrances, and medicinal products that have therapeutic qualities. In addition, hemp seeds are nutritious and can be added to the diet. In chapter one of this thesis, phytoremediation is reviewed to explain the remediation process. This review includes explaining the different phytotechnologies that are employed by plants which depend on the plant used and the type of pollutant encountered. Chapter one also reviews hemp, its history, biology, and the properties that make it a viable choice for phytoremediation. Chapter two of this thesis is an experimental chapter presenting data for testing hemp seedlings with four different oxyanions: arsenate (As), molybdate (Mo), vanadate (V), and tungstate (W). The parameters considered were biomass, chlorophyll content, chlorophyll fluorescence, pollutant accumulation levels, and pollutant fate. Brassica juncea (Indian mustard) was used as a reference phytoremediation species. The findings of this thesis study present promising results for hemp as a potential remediator. Arsenic was found to accumulate in the root at levels up to 2700 mg kg-1 DW. Tungsten also accumulated in the root at levels up to 3100 mg kg-1 DW. In both tests, hemp performed well, judged from photosynthetic measurements and relative chlorophyll content, but reduced biomass started at treatments with 3 and 24 mg As L-1 in the shoot and root respectively, and 40 and 80 mg W L-1 in the shoot and root, respectively. Molybdenum accumulated in the shoot at levels up to 4900 mg kg-1 DW and in the root at levels up to 2600 mg kg-1 DW. Biomass reduction of Mo started at treatment with 40 mg Mo L-1 for both shoot and root, while photosynthetic measurements and relative chlorophyll content remained unchanged. Lastly, V accumulated in the root at levels up to 2100 mg V kg-1 DW. Interestingly, hormesis (stimulated growth) was observed in hemp supplied with V: biomass increased at all tested levels. From this study, it was concluded that hemp may have potential for phytoremediation in cleaning contaminated sites with the four elements tested. Hemp performed competitively with the popular phytoremediation species, Indian mustard (Brassica juncea L.) in all levels tested for Mo, V, and W. Hemp's economic recovery with clean post-harvest biomass may offset phytoremediation costs giving this species a unique advantage over other popular phytoremediation choices.
Keywords: hemp; phytoremediation; vanadium; molybdenum; arsenic; tungsten